Rationale as an Innovative Learning Application to Improve Students Critical Thinking in Argumentative Writing - Rahmah, Nova Alfi Laili; Munir, Ahmad; Anam, Syafiul (Universitas Malikussaleh, 2019)
This study is about the effect of rationale application usage as innovative learning application to help the students being critical thinker in writing argumentative text. It was attempted to investigate (1) whether there is any significant difference between students reasoning ability, (2) whether there is any significant difference between students structuring ability, and (3) whether there is any significant difference between students analyzing ability who are taught by using rationale application as found in their argumentative writing and those who are not taught without using rationale. To do so, a quasi-experimental designed was administered to a sample of University students (N=50). In order to answer the research questions, the data are analyzed by using independent sample t-test. SPSS 21 is used to do those statistical analysis. In conclusion, the findings showed that rationale application can be chosen as an alternative media of improving critical thinking in argumentative writing. It was proved by the findings of the study that bring us to the point that there was a significant difference on the students critical thinking in some aspects (reasoning, structuring and analyzing ability) as found in their argumentative writing between learners in experimental and control group. Learners who are given rationale application treatment achieve higher than those who are given conventional method.